Banana root system: towards a better understandingfor its productive management/Sistema radical del banano: hacia un mejor conocimiento para su manejo productivo: Proceedings of an international symposium held in San José, Costa Rica, 3-5 November 2003/Memorias de un simposio internacional, San José, Costa Rica, 3-5 noviembre 2003 - Turner, David W.; Rosales, F.E.; International Network for the Improvement of Banana and Plantain (2005)
The objective of the symposium was to present the state of the art knowledge on the functioning of the Musa root system and its interrelationships with micro-organisms and pests, and to propose ways to improve root health. The papers present work done on cells as well as whole plants, and short-term studies as well as ones that cover many years and multiple locations.